Effect of pathogenic yeasts on human platelet aggregation - Neiva,Teresinha de Jesus Carvalho (2003)
We investigated the effects of Candida albicans, Cryptococcus neoformans and the respective culture supernatants on human platelet aggregation (PA). Both yeasts were unable to aggregate the platelets directly. On the other hand, cells of these yeasts significantly (P < 0.01) inhibited PA at concentrations equal to or higher than 1 x 10(6) cells/mL for C. albicans and equal to or higher than 1 x 10(5) cells/mL for C. neoformans. When the supernatants of one-week broth cultures were added to the activated platelets no inhibition in aggregation was observed. Apparently somatic components of these yeasts, but not their metabolic products, exert an antagonistic effect on the aggregation of human platelets, possibly aiding the fungi in their evasion of the microbicidal defense system during vascular dissemination.